1977
DOI: 10.1021/jm00212a014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral activity of certain thiazole C-nucleosides

Abstract: A general reaction of glycosyl cyanides with liquid hydrogen sulfide in the presence of 4-dimethylaminopyridine to provide the corresponding glycosylthiocarboxamides is described. These glycosylthiocarboxamides were utilized as the precursors for the synthesis of 2-D-ribofuranosylthiazole-4-carboxamide and 2-beta-D-ribofuranosylthiazole-5-carboxamide (23). The structural modification of 2-beta-D-ribofuranosylthiazole-4-carboxamide (12) into 2-(2,3,5-tri-O-acetyl-beta-D-ribofuranosyl)thiazole-4-carboxamide (15)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
2

Year Published

1978
1978
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(57 citation statements)
references
References 13 publications
3
50
0
2
Order By: Relevance
“…Preliminary studies of tiazofurin 2 (33) indicated that it possesses a spectrum of antiviral activity in cell culture similar to, but somewhat less potent than, that of ribavirin I (1-P-D-ribofurant Contribution no. 1669, Army Research Program on Antiparasitic Drugs. osyl-1,2,4-triazole-3-carboxamide) and that it has a significant activity against several experimental neoplasms, including those of the lung (15,18,26).…”
mentioning
confidence: 99%
“…Preliminary studies of tiazofurin 2 (33) indicated that it possesses a spectrum of antiviral activity in cell culture similar to, but somewhat less potent than, that of ribavirin I (1-P-D-ribofurant Contribution no. 1669, Army Research Program on Antiparasitic Drugs. osyl-1,2,4-triazole-3-carboxamide) and that it has a significant activity against several experimental neoplasms, including those of the lung (15,18,26).…”
mentioning
confidence: 99%
“…The discovery, that tiazofurin (2-β-D-ribofuranosylthiazole-4-carboxamide, 1 possesses antitumor activity 1 and is also endowed with broad-spectrum antiviral activity, 1,2 led to the synthesis of several tiazofurin derivatives, including analogs 2 and 3. [3][4][5] In more recent studies, a series of isomeric dideoxynucleosides was synthesized in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations used in this paper: 3-AB, 3-aminobenzamide; ADPribose, adenosine diphospho-ribose; BCNU, 1,3-bis(2-chloroethyl)-1-nitrosourea; DMS, dimethylsulfate; GMP, guanosine 5'-monophosphate; IMP, inosine 5'-monophosphate; MNNG, N-methyl-N'-nitro-N-nitrosoguanidine; NMN, nicotinamide mononucleotide; SAD, selenazofurinadenine dinucleotide; Sel, selenazofurin; TAD, tiazofurin-adenine dinucleotide; Taz, tiazofurin. boxamide) are synthetic "C" nucleoside analogs with potent antineoplastic activity in experimental murine and human tumors (1)(2)(3)(4)(5). They are highly effective in treating a variety of murine tumors including L1210 leukemia, P388 leukemia, and the highly resistant Lewis lung carcinoma (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…boxamide) are synthetic "C" nucleoside analogs with potent antineoplastic activity in experimental murine and human tumors (1)(2)(3)(4)(5). They are highly effective in treating a variety of murine tumors including L1210 leukemia, P388 leukemia, and the highly resistant Lewis lung carcinoma (1)(2)(3)(4). They are also effective in vitro against several human tumors including the human colon adenocarcinoma line LoVo/L and the human promyelocytic leukemia cell line HL-60 (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation